Um estudo comparativo da micro e da macroestrutura de narrativas orais na lesão de hemisfério esquerdo e direito e sua relação com volumetria cerebral - Schneider, Fernanda (2018)
This research aims to analyze the micro and macrostructure in the oral production of three narratives, produced from a sequence of pictures, comparing the performance of participants with right hemisphere damage (RHD) and participants with left hemisphere damage (LHD) with the performance of control groups. Furthermore, the linguistic analysis was related to data of memory constructs (working and semantic), reading and writing habits and brain volumetry. The research is divided into Study 1 and Study 2. For Study 1, 32 adult participants who suffered ischemic stroke were selected (with a minimum of four months before collection) to compose the experimental group – 16 participants in LHD and 16 participants in RHD aged between 50 to 79, with a minimum of two and maximum of 12 years of schooling; and 16 participants within the health control (CG), paired in age and schooling with the clinics. From these, 10 participants of each group – capable to perform magnetic resonance imaging exams – were selected to make part of Study 2, which relates data from neuropsychological and linguistic tasks to data from structural neuroimaging – known as Voxel-based morphometry (VBM). Inferential analysis in Study 1 showed that post-stroke writing and naming variables influenced significantly the performance in the micro and macrostructure, with the clinical group obtaining a statistically inferior result in the microstructure in relation to the CG. In relation to the macrostructure, there was also a significant correlation in the Digit span (working memory) in the three groups, but without statistical difference between the groups. In Study 2, LHD performance was significantly lower in the microstructure compared to RHD and CG. In the microstructure, in Study 2, the brain regions were grouped into four major components (CP). Thus, in the inferential analysis, all the main components of the brain areas (CP1, CP2, CP3 and CP4) showed a correlation with the microstructure variable, as well as significantly correlated post-stroke writing and naming variables. In the macrostructure, in Study 2, the variables that presented a statistically significant effect were GLH, writing habits after stroke, working memory and interaction between GLH variables and one of the main components of brain area (CP3). The parahippocampal area of the RH showed a correlation with CP3, which implies that this region significantly differentiates LHD from RHD in macrostructure processing. Thus, based on the analyzes and discussions proposed in the study, it was intended to contribute to the understanding of micro and macrostructure characterization in the production of oral narratives in right hemisphere and left hemisphere lesions and their correlation with cognitive constructs, more specifically of working memory and semantics and volume of brain areas involved. The work sought to advance in the discussion surrounding hemispheric specialization for the processing of oral discourse, especially of narratives, for the benefit of future research and clinical intervention.